Analisis Hukum Atas Penolakan Isbat Nikah Dalam Perkawinan Siri Dan Penetapan Status Anak Sah Dalam Studi Kasus Putusan Nomor: 129/Pdt.P/2024/PA.Bsk - Aswandi, Aswandi; Elimartati, Elimartati; Nofialdi, Nofialdi; Zulkifli, Zulkifli; Yunarti, Sri (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2026)
This study analyzes Batusangkar Religious Court Decision No. 129/Pdt.P/2024/PA-Bsk, which simultaneously rejected a request for marriage confirmation (isbat nikah) but granted a request to determine the child's status as legitimate. This case is interesting because it reflects the tension between the principle of legal certainty of marriage and the protection of children's rights in religious court practice in Indonesia. This study used a qualitative, analytical, and descriptive approach with field research methods. Primary data were obtained through in-depth interviews with the three judges who heard the case and the applicants. In addition, the researcher analyzed the decision documents and case files. Secondary data came from the Marriage Law, the Compilation of Islamic Law (KHI), Constitutional Court Decision No. 46/PUU-VII/2010, literature on munakahat fiqh (jurisprudence), and the concept of maqashid sharia. The results indicate that the panel of judges rejected the marriage confirmation request because the applicants' marriage violated the provisions prohibiting marriage as stipulated in Article 40 (a) of the KHI in conjunction with Article 9 of Law Number 1 of 1974 concerning Marriage. One of the parties is still bound by a previous marriage, potentially leading to the practice of polyandry and undermining the sanctity of the institution of marriage. Nevertheless, the judge granted the child's status as legitimate, primarily considering the child's best interests and the principle of welfare (maslahah). The judge argued that the child should not be held responsible for the parents' mistakes. This granting of the child's status provides legal certainty for the child to obtain a birth certificate, family card, rights to maintenance, guardianship, and inheritance rights. This decision represents a harmony between positive legal certainty and the maqasid sharia, particularly hifz al-nasl (protection of offspring). This study concludes that the judge applied a progressive and humane approach in resolving the conflict between the validity of the marriage and the protection of children's rights.